الرواة الذين اختلف فيهم حكم الإمام الذهبي - كشحه عبد الرزاق (University of Eloued جامعة الوادي, 2023)
يتلخص مضمون هذا البحث في دراسة الرواة الذين تغير فيهم حكم الإمام الذهبي في كتبه - نماذج مختارة - من الثقة إلى الصدوق، ومن الصدوق إلى الثقة ، وقمنا بمنهج استقرائي بجمع الأقوال في كل راو تبيَّنتْ لنا بعض النتائج أنه كان يُدافع أحيانًا عن بعض الرواة إذا اتهموا ببدعة أو قدح في الديانة، وأحيانًا يُبين حالهم في الضبط والإتقان ، وإن كانت عند التأمل أن مادة هذا البحث منثورة في بطون كتب نقد الرجال إلا أنه بدراسة هذا البحث نكون ـــ إن شاء الله ـــ قد قرَّبنا مادة هذا الموضوع، وبالله التوفيق.This research is summarized in the study of some narrators in whom the rule of Imam al - Dhahabi changed in his books from trustworthiness to trust, and from trustworthiness to trust. We took an inductive approach by collecting the sayings of each narrator, and we found some results that he sometimes defended some narrators if they were accused of heresy or defamation in religion, and sometimes showed their state of discipline and mastery. Although when contemplating that the material of this research is scattered in the stomachs of books of criticism of men. However, by studying this research, we hopefully have brought the material of this topic closer, and God bless yo
مدذرة ماستر علوم حديث
Keywords: الرواة-; صدوق-; ثقه; الجرح و التعديل; Narrators; Honest; Trustworthy; Al-Jarh and Al-Ta'deel